Regional and disease-related differences in properties of the equine temporomandibular joint disc. (3rd January 2019) - Guerrero Cota, Jose M.; Leale, Dustin M.; Arzi, Boaz; Cissell, Derek D.
Abstract: Temporomandibular joint (TMJ) disorders affect up to 12% of the human population, and naturally occurring TMJ diseases are increasingly recognized in animals. The TMJ disc plays a major role in TMJ disorders in people, but little is known about its role in TMJ pathology in animals. This study characterizes differences in properties of equine TMJ discs associated with age, disc region, and presence of TMJ osteoarthritis (OA). Discs were dissected from both TMJ's of sixteen horses euthanized for reasons unrelated to this study. Each joint was grossly evaluated and scored as normal, mild OA, or severe OA. Samples from the rostral, caudal, lateral, central, and medial regions of the disc were subject to compressive testing, quantitative biochemistry, and histology. Samples from the lateral, central, and medial region were tested for tensile properties in the rostrocaudal and mediolateral directions. We found that the equine TMJ disc is highly anisotropic, and its glycosaminoglycan (GAG) content and compressive stiffness vary between disc regions. The disc also exhibits increasing GAG content and compressive stiffness with increasing age. While equine TMJ disc properties are generally similar to other herbivores, greater compressive stiffness throughout the disc and greater GAG content in its rostral region suggest that mechanical demands on the TMJ disc differ between horses and other species. Importantly, a region-specific decrease in compressive stiffness was observed associated with joint disease and corresponded to cartilage erosions in the underlying condylar surface.